The Effectiveness of Interactive PowerPoint Media in Civics Education for Grade XI Students of SMAN 3 Sungai Kakap - Hemafitria, Hemafitria; Firmansyah, Syarif; Suci Maelliya Angraini; Dwi Handoko, Wahyuda (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2025)
This research focuses on evaluating the impact of interactive PowerPoint media on the learning outcomes of Grade XI A students. Utilizing the Classroom Action Research (CAR) method, the study was carried out in two cycles, each involving planning, execution, observation, and reflection. In the first cycle, PowerPoint was used in a conventional manner, which led to minimal student involvement—only 5 out of 26 students (19.23%) met the learning criteria. After evaluating the results, the second cycle introduced more interactive features, such as animations, contextual visuals, hyperlinks, and guiding questions, alongside more participatory teaching methods. This approach significantly increased engagement, with 76.92% (20 out of 26) of students achieving the Minimum Mastery Criteria (KKM). The study concludes that interactive PowerPoint enhances student-centered learning and aligns with 21st-century educational goals. Its innovation lies in applying interactive media specifically to civic education (PPKn), traditionally taught through lectures, thus fostering greater student interaction and improved academic performance.